Aircraft trailing vortices - cirrus cloud interaction and green aircraft technology: an overview - Djojodihardjo, Harijono (IEEE, 2013)
Anthropogenic solutions that can be offered by Aerospace Technology to address environmental changes known are known as green technology initiatives. Such initiatives, however, may only provide partial or temporary solutions, as learned from mankind experience through the ages. To this end, basic principles governing physical changes occurring in the earth's environment will be reviewed. In the efforts to intervene such process and thus maintaining the sustainability of the earth's environment, some scientific and technological guidelines to comprehend the natural phenomena and global changes are reviewed and discussed. In particular, efforts devoted to aircraft technology and aviation, will be elaborated in view of the goal of maintaining the sustainability of the earth's environment. In addition to fuel burn, particular considerations are given to contrail and trailing vortices.